Scrambler therapy for treatment of poststroke pain - Robert Stowell‐Campos; Erin Lawrence; Elisabeth Breese Marsh; Dawn Merbach (Annals of Clinical and Translational Neurology)
Abstract Objective Strokes involving sensory pathways can result in contralesional pain syndromes often refractory to pharmacologic interventions. Scrambler therapy (ST) is a noninvasive electroanalgesia device used to treat pain caused by peripheral neuropathy; however, data are scarce regarding its use in conditions secondary to central nervous system pathology. We evaluate the efficacy of ST to treat poststroke pain. Methods Twenty patients with a history of prior stroke resulting in contralesional pain were randomized to receive ST or Sham as an adjunct to their stable medication regimen. Participants underwent 5 consecutive daily 40‐min sessions. The study was blinded to patient and assessor. Pain scores (0–10) were recorded at baseline, pre‐ and postsession, and 4 weeks after final treatment. Student's t‐tests compared differences in the mean change in pain score between groups immediately post‐treatment #5, and at 4‐weeks. The chi‐squared analysis compared the proportion of patients in each group with >50% pain reduction. Results Participants randomized to ST had a mean change in pain score of −3.73 (SD 2.85) postintervention and −2.57 (SD 2.07) at 4 weeks, while the Sham group had a mean change in score of −0.94 (SD 1.36) and −0.25 (SD 0.84) (p between groups = 0.012, 0.004, respectively). Significantly more participants treated with ST reported a >50% reduction in pain immediately postintervention compared to Sham (70% vs. 10%, p = 0.006), but not at follow‐up (30% vs. 10%, p = ns). Interpretation ST may effectively decrease poststroke pain compared to Sham. Larger studies are needed to evaluate confounders such as stroke location, time from stroke, and concomitant treatment with medications.